Proteome-wide analysis of protein disorder in Triticum aestivum and Hordeum vulgare. (February 2020) - Choura, Mouna; Rebaï, Ahmed; Hanin, Moez
Graphical abstract: Highlights: We present the first large-scale study of the repertoire of IDPs in Triticum aestivum and Hordeum vulgare proteomes. Results show that proteins in T. aestivum are significantly more disordered than those of H. vulgare . IDPs in T. aestivum and H. vulgare are involved in regulation of cellular and biological processes up on response to stress. Abstract: There has been an increasing interest in Intrinsically Disordered Proteins (IDPs) ever since it was proven that they are ubiquitous and involved in key cellular functions. Interestingly, they have shown a large abundance in complete proteomes. In the current study, we have investigated the first large-scale study of the repertoire of IDPs in Triticum aestivum and Hordeum vulgare proteomes, in order to get insight into the biological roles of IDPs in both species. Results show that proteins in T. aestivum are significantly more disordered than those of H. vulgare . Moreover, the data revealed that DNA/RNA binding domains, co-factors, heme, metal ions binding domains, ATP/GTP binding proteins, ligands, linker domains and repeats, other domains typical to transcription factors such as zinc finger, F-box domain, homeodomain-like, l -domain like and chaperones, are predominantly present and co-occur in disordered proteins in T.aestivum and H.vulgare . The Gene Ontology analysis revealed that IDPs in T. aestivum and H. vulgare are mainly involved in regulation of cellular and biological processes up on response to stress. In future, this study may provide valuable information while considering IDPs in understanding the organism complexity and environmental adaptation.